2010
DOI: 10.1007/s00464-010-1169-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategy for recurrent or residual colorectal tumors after endoscopic resection

Abstract: ESD is safe and effective for the treatment of recurrent or residual colorectal tumors. However, because of its technical difficulty, the en bloc resection rate is lower than that for the treatment of nonrecurrent lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 24 publications
3
66
3
1
Order By: Relevance
“…We previously reported that the recurrent or residual lesions did not show increased levels of histological atypia; they were mainly recognized as adenomas, even when the patients had been initially diagnosed with intramucosal carcinoma [11]. Thus, the efficacy of EPMR for certain types of lesions was confirmed.…”
Section: Introductionmentioning
confidence: 83%
“…We previously reported that the recurrent or residual lesions did not show increased levels of histological atypia; they were mainly recognized as adenomas, even when the patients had been initially diagnosed with intramucosal carcinoma [11]. Thus, the efficacy of EPMR for certain types of lesions was confirmed.…”
Section: Introductionmentioning
confidence: 83%
“…Compared to the classical OTSC the clip used in the FTRD has additional lateral teeth in order to ensure a safe closure of the defect before resection. The FTRD cap is longer compared to the standard OTSC (23 mm vs 6 mm) and thus accommodates a tissue volume of approximately 3 cm 3 . This allows the capture of lesions of up to 30 mm in diameter.…”
Section: Description Of the Ftrd Devicementioning
confidence: 99%
“…Although recurrent disease after endoscopic resection can be treated with ESD, equivalent long-term outcomes were seen in a retrospective study where further EMR was permitted [85].…”
Section: Emr Versus Esd: Complimentary Strategiesmentioning
confidence: 84%